Analysisof Causes of High Water Content in X Block Reservoirs and Treatment Strategies - Xi, Yongzhao; Lan, Huayan (International Journal of Natural Resources and Environmental Studies, 2025)
In response to the problem of high water content in the Chang 2 oil reservoir in Block The analysis results show that water breakthrough in oil wells includes edge and bottom water, injection water, and casing damage water breakthrough. The reason for the high water content in the Chang 2 reservoir oil wells in Block.